Differences between unipolar mania and bipolar‐I disorder: Evidence from nine epidemiological studies. (14th December 2018) - Angst, Jules; Rössler, Wulf; Ajdacic‐Gross, Vladeta; Angst, Felix; Wittchen, Hans Ulrich; Lieb, Rosalind; Beesdo‐Baum, Katja; Asselmann, Eva; Merikangas, Kathleen R; Cui, Lihong; Andrade, Laura H; Viana, Maria C; et al.
Abstract : Objectives: Although clinical evidence suggests important differences between unipolar mania and bipolar‐I disorder (BP‐I), epidemiological data are limited. Combining data from nine population‐based studies, we compared subjects with mania (M) or mania with mild depression (Md) to those with BP‐I with both manic and depressive episodes with respect to demographic and clinical characteristics in order to highlight differences. Methods: Participants were compared for gender, age, age at onset of mania, psychiatric comorbidity, temperament, and family history of mental disorders. Generalized linear mixed models with adjustment for sex and age as well as for each study source were applied. Analyses were performed for the pooled adult and adolescent samples, separately. Results: Within the included cohorts, 109 adults and 195 adolescents were diagnosed with M/Md and 323 adults and 182 adolescents with BP‐I. In both adult and adolescent samples, there was a male preponderance in M/Md, whereas lifetime generalized anxiety and/panic disorders and suicide attempts were less common in M/Md than in BP‐I. Furthermore, adults with mania revealed bulimia/binge eating and drug use disorders less frequently than those with BP‐I. Conclusions: The significant differences found in gender and comorbidity between mania and BP‐I suggest that unipolar mania, despite its low prevalence, should be established as a separate diagnosis both for clinical and research purposes. In clinical settings, the rarer occurrence of suicide attempts, anxiety, and drug use disorders among individuals with unipolar mania may facilitate successful treatment of the disorder and lead to a more favorable course than that of BP‐I disorder.